Assessment of the perception of the environmental management system in agroindustry - Fernandes, Edson Vagner Godoi; Silva, Clairton Tadeu Bidtinger da; Lótici, Karine Marosin (Revista Gestão da Produção Operações e Sistemas, 2008)
The objective of this study is to identify the perception of collaborators at an agroindustry located in Marau, RS, with regard to the Environmental Management System. Comparative analysis between the collaborators expectation and perception will be used. The theoretical basis for the study is found in authors related to the environmental and natural resource areas and authors who describe NBR ISO 14001. The case study method was used with data collected from a sample of 163 questionnaires answered by a population that consisted of operational collaborators, technicians and supervisors, uniformly distributed over the companys three work shifts. A comparative analysis between the collaborators expectation and perception in relation to the environmental management system indicated that expectations exceed real perceptions of results presented by the system, generating a large number of opportunities for improvement. Keywords: Environmental Management; NBR ISO 14001; Natural Resources.